Molecular analyses of antimicrobial resistance characteristic of Klebsiella pneumoniae strain CJK 500 2.1.2 isolated from Cikijing River - Irawati, Wahyu; Ong, Michael Kayne; Purnomo, Jonathan Suciono; Jo, Juandy (Universitas Gadjah Mada, 2026)
Many areas in Indonesia face severe pollution from copper and antibiotics, impacting microbial diversity and underscoring the need for effective remediation strategies. Harnessing of copper- and antibiotic-resistant bacteria has become a promising approach. This study evaluates the antimicrobial resistance (AMR) profile of copper-accumulating Klebsiella pneumoniae strain CJK 500 2.1.2 as a bioremediation agent candidate. Whole-genome analysis of K. pneumoniae CJK 500 2.1.2 revealed multiple AMR genes, primarily encoding efflux pumps, with one fieF gene facilitating resistance to heavy metals. The disk-diffusion assay highlighted multidrug-resistance traits, regardless of CuSO4. Notably, increased cefoxitin resistance in the presence of CuSO4 and intermediate susceptibility to tetracycline were observed, which was corroborated by a broth microdilution assay. The genome analysis identified 22 virulence factors (VFs) and 16 insertion sequences (ISs), with some ISs located near AMR and VF genes, suggesting possible horizontal gene transfer (HGT). Overall, K. pneumoniae CJK 500 2.1.2 showed a potential as a model study for bioremediation research on genetically engineered microorganism (GEM). Through risk assessment, GEMs have the possibility to be applied to copper and antibiotics bioremediation.